Studies on grain weight, protein content and germinating performance of the grains from different ear positions for barley - YIN Chen; ZHANG Guo-ping (浙江大学学报. 农业与生命科学版, 2001)
Grain weight, protein content and germinating performance of the barley grains from different ear positions (top, middle and bottom) were measured. It is showed that grain weight of middle-positioned grains is higher than that of both top- and bottom-positioned grains for plants with different ear number per plant and for 5 cultivars. The top grains in the plants with one ear, the middle grains in the plants with two ears and the bottom grains in the plants with three ears, have the highest protein content among all grains on the main shoot ears, respectively. On an average of all grains, including main shoot and tiller ears, Xiumai-3 contains the highest protein content, while 97-33 is the lowest. In a main shoot ear, top grains contain the highest protein content. The top grains germinate fast and best, irrespective of the ear number per plant. Among the cultivars in study, 99-18 shows the best germinating performance and 92-11 the worst.